Peran Ibu Rumah Tangga dalam Meningkatkan Perekonomian Keluarga di Desa Bontomanai Kabupaten Bulukumba - Auliya Rukmana Amar (Jurnal Riset Akuntansi, 2025)
The role of a mother is not only to take care of the household and household activities, but also to help the family economy. The reason housewives have a dual role in the family is, first, because of economic pressure, second, when the husband dies or the wife divorces, third, to fill free time and develop skills. This research is a research that uses qualitative methods. The subjects of this study are six housewives who work to earn a living. Data collection is carried out by observation, interviews, and documentation. The data analysis used is data reduction, data presentation and verification or conclusion drawn. The validity test of the data used in this study is membercheck, and triangulation. The results of the study show that the role of housewives who participate in earning a living greatly affects the improvement of the economy. This can have a positive impact on housewives in Bontomanai Village, Bulukumba Regency, namely increasing family income and fulfilling daily needs.